The Implementation of Dictation (Tingxie) in Chinese Online Learning for Beginner-Level Students - Nanda Lailatul Qadriani (JURNAL Al-AZHAR INDONESIA SERI HUMANIORA, 2023)
Dictation (tīngxiě) is commonly applied to evaluate students' ability to master Chinese characters. However, dictation is challenging to use in online learning because lecturers do not have full control over the conditions around students when dictation is carried out. Students tend to think more about a "strategic position" to putting notes during dictation than preparing and memorizing Chinese characters. Therefore, it is necessary to adjust the types of dictation questions in online learning. This study is a classroom action research which consists of 4 stages: planning, implementing, observation, and reflection. Researchers designed four types of dictation questions that applied to the Writing Proficiency course for beginner-level Chinese Language and Culture Study Program students at the University of Al Azhar Indonesia. Research data sources from observations, questionnaires and tests. The results showed that the design of the applied dictation question types effectively reduced the opportunity for students to cheat during dictation. In addition, this dictation method is also effective for practising Chinese writing skills and students' mastery of Chinese strokes and writing order.Keywords - Chinese character; dictation; tingxie; online learning; Chinese language.